2014
DOI: 10.1152/japplphysiol.00663.2013
|View full text |Cite
|
Sign up to set email alerts
|

Timing of return from altitude training for optimal sea level performance

Abstract: While a number of published studies exist to guide endurance athletes with the best practices regarding implementation of altitude training, a key unanswered question concerns the proper timing of return to sea level prior to major competitions. Evidence reviewed here suggests that, altogether, the deacclimatization responses of hematological, ventilatory, and biomechanical factors with return to sea level likely interact to determine the best timing for competitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
(67 reference statements)
1
37
0
Order By: Relevance
“…Alterations in the biomechanical and neuromuscular components associated with force production are some of the factors recently suggested by Chapman et al [36] that influence changes in performance following altitude training. According to this, the improvement in speed movement can also be attributed to an enhanced firing frequency of motoneurons and spinal reflexes.…”
Section: A Description Of the Mechanisms And Metabolic Factors Relatementioning
confidence: 99%
“…Alterations in the biomechanical and neuromuscular components associated with force production are some of the factors recently suggested by Chapman et al [36] that influence changes in performance following altitude training. According to this, the improvement in speed movement can also be attributed to an enhanced firing frequency of motoneurons and spinal reflexes.…”
Section: A Description Of the Mechanisms And Metabolic Factors Relatementioning
confidence: 99%
“…An athlete's busy travel schedule, external commitments, and competition program make it difficult to time competing at sea level after an altitude training camp. Chapman et al (2014), suggested that if an athlete completes a 4-week altitude training camp, followed by a short time (~7-14 days) at sea level to compete, returning to altitude even for a short time may mitigate or delay the effects of neocytolysis by re-establishing EPO levels, although this has not been proven. This is not for added erythropoiesis, as is typically done with altitude residence, but more to delay the selective destruction of reticulocytes due to lower than baseline EPO concentrations, as a result of the athlete just remaining at sea level.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Brief periods of severe hypoxia have been suggested as a potential method to prevent the sudden decrease in EPO (Pottgiesser et al., ). This in turn would preserve the hematological acclimatization response for a longer time, thereby expanding the window for endurance training and optimal competition racing (Chapman et al., ). Figure illustrates the previous investigations that have demonstrated an increase in EPO as a result of hypoxic exposures lasting 5 min to 5.5 h (Eckardt et al., ; Knaupp et al., ; Rodríguez et al., ; Ge et al., ; Niess et al., ; Friedmann et al., ; MacKenzie et al., ; Wahl et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that aerobic capacity usually peaks within 1-3 weeks after the end of other methods of altitude training than IHT (8). After that, aerobic capacity tends to decline (8).…”
Section: Introductionmentioning
confidence: 96%